SOLVENT EXTRACTION FOR OILY SOIL DECONTAMINATION UTILIZING CHEMICAL SOLVENTS AND BIOSURFACTANT - Fitriyani, Lely
Even though solvent extraction has been known for decades to various treatment process industries, the implementation of this process as a decontamination method as known also as soil washing should be studied further. This research study about optimation of solvent extraction for several parameters such as mixing method, solid to solvent ratio, temperature, and type of solvents. Implementation of biosurfactant, besides many others chemical solvent was one of highlighted observation area. While the optimation of parameters also conducted for biosurfactant, the purpose to seek its implementation affect to the Total Petroleum Hydrocarbon (TPH) removal and toxicity impact for residual solid after solvent extraction process has been implemented as a decontamination method for oily contaminated soil. TPH became the main focus of this study. However, other aspects such as metal and heavy metal content were also studied. Observation statistics were also conducted to see the significance of key parameters during the treatment process. Shaking and centrifugation as mixing method that has been selected as optimum method for solvent extraction process, temperature gave optimum performance of solvent extraction process at 50oC, while increasing the solvent ratio at some point would not efficient to increase TPH removal the optimum ratio obtained at 1:3. Statistics analysis that has been run also confirmed that temperature and solid to solvent ratio provided less significant contributing factor for solvent extraction process, other than type of solvent itself and its compatibility to contaminated soil. GC-FID, FTIR spectrofotometry, XRF analyzer, and TCLP test has been run to examine hydrocarbon composition, metal, and leaching metal content of residual soil after decomtamination process. Germination index tests were also conducted to know toxicity impact of residual solid for seed germination at post decontamination of oily soil. Result indicated that post decontamination, TPH removal efficiency could reach maximum 96% for chemical solvent and 78% of biosurfactant for single stage of extraction and toxicity of soild reduce significantly not only as concentration and hydrocarbon structure, but also able to increase seed germination index of contaminated soil.